Mid-Term Outcomes of Cemented or Uncemented Total Hip Arthroplasty for Failed Proximal Femoral Nail Antirotation Following Intertrochanteric Femur Fractures: A Retrospective Observational Study - Tao Huang; Shi Zhang; Xinhang Liu; Gang Lv; Heng Huang; Shuxin Wang; Mingdong Zhao; Min Xiong; Weiguang Yu; Qiuxia Cheng; Ting Huang (Geriatric Orthopaedic Surgery & Rehabilitation, 2022)
Introduction The aim of this retrospective study was to assess the clinical outcomes of cemented or uncemented total hip arthroplasty (CTHA or UTHA) following prior failed proximal femoral nail antirotation (PFNA) fixation in patients with intertrochanteric femur fractures (IFFs). Materials and methods Data from 244 patients with IFFs who experienced a conversion of PFNA to CTHA (n = 120) or to UTHA (n = 124) due to screw cut-out, mal/nonunion, or osteonecrosis during 2008-2018 were retrospectively analyzed. Follow-up occurred 1, 3, 6, and 12 months postoperatively and yearly thereafter. The primary outcome was the incidence of orthopedic complications; the secondary outcome was the Harris hip score (HHS). Results The median follow-up was 60 months (range, 50-67 months). The incidences of orthopedic complications were 10% in the PFNA to CTHA group and 19.3% in the PFNA to UTHA group (P = .040). Significant differences were also observed regarding the incidence of prosthesis revision (1.7% for PFNA to CTHA vs 7.2% for PFNA to UTHA, P = .036). From the three years after conversion surgery to the final follow-up, significant differences were detected in HHS between groups (each P < .05). At the final follow-up, a statistically significant difference was detected in the HHS (79.54±18.85 for PFNA to CTHA vs. 75.26±18.27 for PFNA to UTHA, P = .014). Conclusion The results of the study may demonstrate a significant statistical advantage with respect to the orthopedic complication rate and HHS in favor of CTHA compared to UTHA in patients with failed PFNA.